Duduk dan Tonton: Meet-and-Q&As with Filmmakers - Chong Lee, Yow; Abdullah Sofiuddin, Mah (Mini Film Festival, 2021)
In collaboration with SeaShorts Film Festival, Mini Film Festival had screened FIVE (5) Southeast Asian (SEA) shorts of which some of them had travelled as far as France (Clermont-Ferrand FF) and South Korea (Busan IFF) to meet their respective audiences, namely: